THE IMPACT OF EMPLOYEE EMPOWERMENT ON JOB SATISFACTION WITH MODERATING ROLE OF ORGANIZATIONAL POLITICS: A CASE FROM TOBACCO MANUFACTURING SECTOR OF KHYBER PAKHTUNKHWA - Sultan, Fahad; Khan, Muhammad Nawaz; Khalil, Syed Haider; Asim, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to explore the impact of employee’s empowerment on job satisfaction with moderating effect of organizational politics. The data was collected from 150 employees working in Tobacco sector of Khyber Pukhtoon Khwa at different capacity through self-administrated questioner using random sampling technique. The statistical tools (i.e. reliability, correlation and regression) was used to test the hypothesis of the study. The results of the correlation show that there is positive relationship between employee’s empowerment and job satisfaction. While organizational politic has negative relationship with employee’s empowerment and job satisfaction. The result of the regression analysis with moderating technique shown that organizational politics has negative moderating impact on the relationship between employee’s empowerment and job satisfaction. This study analyzes that in political situation only dominant group can enjoy the rewards and rest of the employees suffer which is cause dissatisfaction. The results of this study also line to those researchers who view that organizational politics can negatively affect employee’s empowerment and job satisfaction. Hereafter, on the basis of the results of this study it is recommended that such kind of political activities in organization should be avoided to achieve organizational goals and objectives and create satisfied and empowered workforce. This study provides the basics of organizational politics and the consequences of the perception of organizational politics. This study also provides the pat way that how the management act to prevent political activities in their organizations.